2018
DOI: 10.1111/aji.13053
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor gamma ligands affect NF‐kB and cytokine synthesis in the porcine endometrium—An in vitro study

Abstract: Problem Cytokines, mediators of the immune response, are involved in the regulation of female reproductive processes during the estrous cycle and pregnancy. The present study aimed to investigate the effect of selected peroxisome proliferator‐activated receptor gamma (PPARγ) ligands on the expression of nuclear factor kappa B (NF‐κB) and selected cytokines, such as interleukin (IL)‐1β, ‐4, ‐6, ‐8, ‐10, and the leukemia inhibitory factor, in the porcine endometrium on days 10‐12 and 14‐16 of the estrous cycle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
2
6
1
Order By: Relevance
“…This shows that MMP-2 was upregulated via the increased activity of the NF-kB. This result is consistent with the previous investigations, which showed that the NF-kB activation is increased proliferation, angiogenesis, and apoptosis in endometriosis (Kunicka et al, 2019, Calibasi-Kocal et al, 2019. It has been shown that NF-βB acts via regulation of the MMPs expression in the adhesion and invasion of endometriosis cells on the peritoneal surface (Lee et al, 2010, Gottschal et al, 2002.…”
Section: Discussionsupporting
confidence: 91%
“…This shows that MMP-2 was upregulated via the increased activity of the NF-kB. This result is consistent with the previous investigations, which showed that the NF-kB activation is increased proliferation, angiogenesis, and apoptosis in endometriosis (Kunicka et al, 2019, Calibasi-Kocal et al, 2019. It has been shown that NF-βB acts via regulation of the MMPs expression in the adhesion and invasion of endometriosis cells on the peritoneal surface (Lee et al, 2010, Gottschal et al, 2002.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the ligands did not change IL‐6 mRNA expression, but the PPARα agonist increased IL‐6 protein expression in the mid‐luteal phase of the estrous cycle and at the beginning of implantation. The absence of any associations between mRNA and protein expression in the current study and in our previous research could be attributed to various biological and technical factors, such as differences in mRNA and protein stability, transcriptional and posttranscriptional regulation, and existing feedback, which can suppress mRNA expression through high protein expression and attenuate post‐transcriptional processes through high mRNA content . Further research is needed to determine biological factors that exert the greatest influence on the relationship between mRNA and protein expression …”
Section: Discussioncontrasting
confidence: 46%
“…The procedures for tissue harvesting and culture were described previously . Briefly, tissue explants (200 ± 10 mg) were incubated in the M199 medium (Sigma Aldrich) supplemented with 0.1% BSA fraction V and antibiotics: nystatin (120 IU/mL; Sigma Aldrich) and gentamicin (40, 40 mg/mL; Sigma Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations